Strengthening Adult Literacy Through Creative Writing - Elizabeth Santiago (Adult Education Research Conference, 2021)
This Roundtable will discuss a qualitative study that investigated how creative writing strengthens and deepens the literacy skills of adults. Specifically, the study explores two sub-questions: How can creative writing processes support students’ achievement of personal and/or academic goals? How does a curricular focus on individual storytelling build literacy confidence and/or student agency? Data include: pre- and post-surveys, pre- and post-interviews, curriculum design based on best practices in writing instruction and adult learning, and student writing. The study suggests that creative writing is a viable and effective tool to promote literacy acquisition, build student voice, and support student-centred learning.
Keywords: Adult education; creative writing; high school equivalency; literacy; writing instruction